Fecundity and Gonadosomatic Index of Sucker Throat Catfish, Pseudecheneis sulcata (McClelland, 1842) from the Snow-fed Tamor River in Eastern Nepal - Limbu, Jash Hang; Rajbanshi, Dipak; Kumar, Prakash; Subba, Bharat Raj (Borneo Journal of Resource Science and Technology, 2021)
In comparison to other nations, the Nepalese information on the reproductive biology of hill-stream fish is limited. So, the purpose of the present study was to provide information related to reproductive biology of a hill-stream sucker throat catfish Pseudecheneis sulcata from the snow-fed Tamor River, Nepal. The study was carried out from June 2018 to May 2019. A total of 57 female fish was collected. The fecundity of 22 females was assessed, while the gonadosomatic index was determined using all the collected samples. The absolute fecundity ranged from 2,316 to 7,597 eggs, with an average of 3,660 ± 210. This range of absolute fecundity indicates that Pseudecheneis sulcata is a moderately fecund fish when compared to certain low fecund species and some exceptionally fecund fish with tens of thousands of eggs. Relative fecundity ranged from 65.47 to 129.11 with a mean of 88.98 ± 4.35. The present study demonstrated that absolute fecundity was moderately correlated with total length (r = 0.45) and strongly linked with body weight (r = 0.78), and ovary weight (r = 0.80). Mean gonadosomatic index (GSI) was recorded the highest in January (15.7 ± 1.22%), and showed a decrease in the subsequent month of February (10.3 ± 0.75%), March (6.25 ± 0.28%) and April (1.66 ± 0.40%). The trends of GSI might have indicated that the sucker throat catfish was a batch spawner, with spawning season occuring between January and March.